Utility of Narrow Caliber Echo-bronchoscope in Pre-school Pediatric Population: A case series (with video) - Sharma, Malay (Medknow Publications & Media Pvt Ltd, 2013)
The practical use of EUS in small children below the age of 4 years is not described. The aim of the study was to evaluate the feasibility, safety, and clinical utility of smaller caliber echo-bronchoscope in the management of gastrointestinal, pancreatobiliary, and mediastinal disease in children below 4 years. Consecutive children of age younger than 4 years where EUS was clinically considered useful were evaluated by echo-bronchoscopes. The findings showed that EUS by echo-bronchoscopes is feasible and safe in young children.